Design e acessibilidade em revista de entretenimento para pessoas cegas - Araújo, Bruno Sá de (Brasil, 2023)
The growing number of blind people over the years, both in Brazil and in the world, has led to a greater search for accessible materials, including books, comics and magazines. In parallel to this, digital environments have also been proving to be great means of accessibility for the blind, with increasingly advanced technology and resources that help them both in the search for information as well as reading graphic materials and performing everyday tasks. In view of this context, it was noted the opportunity to propose a solution to the problem of few graphic materials aimed at entertainment that can be enjoyed both by sighted and blind people. In order to obtain a good base for the beginning of the project, a broad research was carried out on the principles of book design, resources aimed at accessibility and the types of existing publications, and the application of interviews and questionnaires with the target audience. Through the data obtained, the production of an entertainment magazine prototype began, which aims to meet the specific objectives established. Then, the magazine prototype was made, being printed and assembled a physical version as well as constructing a digital version, where both are complementary to each other. Finally, the implemented accessibility features were submitted to tests, and it was verified that the material met the needs established at the beginning of the project, culminating in a successful work, and being able to serve as a reference for future initiatives involving accessibility. With this, it was evidenced that the implementation of accessibility in graphic materials is possible and feasible.